Description of Telmatobius brachydactylus tadpole (Anura: Telmatobiidae) - Castillo, Luis (2019)
We describe the tadpole of Telmatobius brachydactylus using specimens from Gosner stages 30 to 41. Telmatobius brachydactylus tadpole is similar to others Telmatobius larvae with pond type morphology, but differs from the sympatric species T. macrostomus by having proportionally a longer tail and significantly a smaller total length between Gosner stages 33 and 41. We recorded for the first time tadpoles of T. macrostomus in syntopy with T. brachydactylus larvae.